Role of Palmitoylation of Postsynaptic Proteins in Promoting Synaptic Plasticity - Matt, Lucas; Kim, Karam; Chowdhury, Dhrubajyoti; Hell, Johannes W. (Frontiers in Molecular Neuroscience, 2019)
Many postsynaptic proteins undergo palmitoylation, the reversible attachment of the fatty acid palmitate to cysteine residues, which influences trafficking, localization, and protein interaction dynamics. Both palmitoylation by palmitoyl acyl transferases (PAT) and depalmitoylation by palmitoyl-protein thioesterases (PPT) is regulated in an activity-dependent, localized fashion. Recently, palmitoylation has received attention for its pivotal contribution to various forms of synaptic plasticity, the dynamic modulation of synaptic strength in response to neuronal activity. For instance, palmitoylation and depalmitoylation of the central postsynaptic scaffold protein PSD-95 is important for synaptic plasticity. Here we provide a comprehensive review of studies linking palmitoylation of postsynaptic proteins to synaptic plasticity.